Study of the properties of the prepared soot from burning Iraqi kerosene - Nadia B. Hussain (Al-Qadisiyah Journal of Pure Science, 2018)
The study involves the synthesis of nanoparticles soot from burning Iraqi kerosene. The prepared particles are treated by three ways: Hydrogen peroxide treatment, hydrochloric acid treatment and sodium hydroxide treatment, then subsequent sonication were performed for 1 hour. Finally, the nano soot particles were characterized by using FTIR, SEM, XRD, EDX and TGA. The change is in nature of bonding and impurities in preparing carbonic materials, which are studied using FTIR spectroscopy. Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) results show significant changes in the structure and morphology of the new materials. Thermal gravimetric analysis (TGA) analyses indicate a gradual weight loss in the temperature range from 0oC to about 700oC.